Human Resource Management Strategy Prediction in Small Business Marketing after Pandemic - Purbaningsih, Yuli; Jamadi, Jamadi; Junianto, Pilifus; Fittriya, Nurul Laili; Ekasari, Silvia (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
Prediction of HR management strategy in small business marketing after the pandemic is the purpose of this study. We believe that every business, both small and large, is very concerned with human resources in marketing all business products. Therefore, we have obtained raw data from electronic searches in several scientific publications, especially HRM and post-pandemic small business marketing governance. We have carefully reviewed the data, involving an in-depth evaluation and coding system so that it is easy for us to answer the questions of this study. Our data publications target journals such as Sagepub, Academic works, Google Books, Taylor and France, and other data sources. We reviewed hundreds of papers to get around 50 journal publications that we have thoroughly reviewed. Based on the discussion of the results, the result is that the human resources department develops rules and processes that promote a fair work environment. Additionally, they settle disputes and listen to employee problems to instill a sense of belonging. All of these factors contribute to the efficient operation of the company and enable workers to perform their best job.HR; marketing; small business; pandemic; publication review